Emerging Technology In English Language Teaching and Learning: Exploring the use of technology in English language learning (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The paper introduce about the use of technology forEnglish language learning does not appear to be restricted to any particularage group as is established by the range of chapters offered in this volume andthe case studies presented here suggest that practitioners are more and moreusing ICT imaginatively within the early years. In many contexts, learners arebeing exposed to a range of technologies from a very early age in the home andby the time they reach nursery age many have developed at least some of thedigital skills that enable them to participate in technology-driven activities